2021
DOI: 10.3390/su13041604
|View full text |Cite
|
Sign up to set email alerts
|

Management Styles and Decision-Making: Pro-Ecological Strategy Approach

Abstract: Management style and decision-making create an organization’s culture and influence its performance also in the pro-ecological dimension. Therefore, this paper’s originality lies in how it explores the effect of management style to inform our understanding of decision-making when using a sustainable approach. However, the cause-and-effect relations between decisions and management style remain vastly unexplored. The paper’s aim is to explore whether the management style serves as a basis for decision-making or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 101 publications
(146 reference statements)
1
29
0
2
Order By: Relevance
“…Furthermore, public governance is not concerned with market competition, it is rather with the need to work collaboratively, as well as participating quickly to find the correct solution at both the community and society levels. As a result of it, modern organisations have to survive in a rapidly changing, challenging environment, and take quick decisions to solve problems [130]. Nowadays, the Mexican government faces large challenges in the face of the COVID-19 pandemic, not just in terms of the economy, but also in terms of many social aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, public governance is not concerned with market competition, it is rather with the need to work collaboratively, as well as participating quickly to find the correct solution at both the community and society levels. As a result of it, modern organisations have to survive in a rapidly changing, challenging environment, and take quick decisions to solve problems [130]. Nowadays, the Mexican government faces large challenges in the face of the COVID-19 pandemic, not just in terms of the economy, but also in terms of many social aspects.…”
Section: Discussionmentioning
confidence: 99%
“…The scope of this project was to produce renewable energy potential maps for Lesotho to assist the Government in the planning and development of renewable energy exploitation and to achieve a concrete step towards attaining a low-emission development pathway. Indeed, the availability of accurate and reliable information plays a key role in the decisionmaking process [47]. In the present case, an energy sector assessment was recognized as essential and it covered different renewable sources such as hydrological, wind and solar.…”
Section: The Project "Renewable Energy Potential Maps For Lesotho"mentioning
confidence: 93%
“…Sulich et al [72] positioned those four styles in a twodimensional graph, as shown in Fig. 2, where the x-axis represents the decision-making participants while the y-axis represents the flexibility and freedom given to the participants.…”
Section: Conceptual Decision-makingmentioning
confidence: 99%